2016
DOI: 10.1111/lang.12189
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Self‐Monitoring in the Second Language

Abstract: Speakers monitor their own speech for errors. To do so, they may rely on perception of their own speech (external monitoring) but also on an internal speech representation (internal monitoring). While there are detailed accounts of monitoring in first language (L1) processing, it is not clear if and how monitoring is different in a second language (L2). Here, we ask whether L1 and L2 monitoring differ and if so, where the differences lie. L1 and L2 might differ in the speed with which monitoring is performed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 74 publications
(91 reference statements)
0
7
0
Order By: Relevance
“…Most notably is the activation account, which proposes that additional activation to the target language can result in fluent bilingual language processing. Other control processes have also been discussed in the literature, such as speech monitoring (Broos et al, 2016). It is important to point out that empirical effects tend to be the result of an accumulation of processes, as probably no effects are process-pure.…”
Section: Requirements Of a Bilingual Inhibitory Control Markermentioning
confidence: 99%
“…Most notably is the activation account, which proposes that additional activation to the target language can result in fluent bilingual language processing. Other control processes have also been discussed in the literature, such as speech monitoring (Broos et al, 2016). It is important to point out that empirical effects tend to be the result of an accumulation of processes, as probably no effects are process-pure.…”
Section: Requirements Of a Bilingual Inhibitory Control Markermentioning
confidence: 99%
“…For repairs in L2 speech, research by Van Hest (2000) showed that different types of repair are observed, depending on proficiency level: low-proficient L2 speakers make more lexical and phonological error repairs while highly proficient speakers use more appropriateness repairs for lexical items (For a recent review comparing monitoring and error repair for L1 and L2 speech, see Broos, Duyck, & Hartsuiker, 2016).…”
Section: Psycholinguisticsmentioning
confidence: 99%
“…Such disadvantages have been demonstrated in both L2 speech production (Ivanova & Costa, 2008; Sadat, Martin, Alario, & Costa, 2012) and L2 speech comprehension (Lagrou, Hartsuiker, & Duyck, 2011). Here, we ask whether there is also a disadvantage in verbal self-monitoring in L2 (see Broos, Duyck, & Hartsuiker, 2016 for a review on L2 verbal self-monitoring). The verbal self-monitoring system is responsible for detecting and correcting speech errors and other problems in speech.…”
Section: Introductionmentioning
confidence: 99%